Pemanfaatan Infografis Sebagai Media Pengemasan Ulang Informasi Koleksi Budaya di Museum Adityawarman - Helmi Ramadhan; Cindy Fatika Sari; Ahsanu Nadiya (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Cultural collection information plays a critical role in strengthening public understanding and cultural literacy in museums. However, the Adityawarman Museum in Padang still relies on conventional interpretive methods such as long textual descriptions and static dioramas, which are less communicative and misaligned with the expectations of today’s digital-oriented visitors. This study employs a qualitative case study approach through field observations, interviews, documentation, and literature review to analyze the potential of infographics as a medium for repackaging cultural information. The findings reveal three major insights: (1) infographics effectively simplify complex cultural narratives and enhance knowledge retention, (2) visual formats increase visitor engagement across diverse literacy levels, and (3) infographics support the creation of accessible, inclusive, and adaptive museum learning environments. Nevertheless, implementation challenges persist, including limited human resources, the complexity of cultural materials, and insufficient digital infrastructure. The study concludes that developing infographic-based interpretation in museums requires an integrated strategy involving staff capacity building, interdisciplinary collaboration, and the formulation of culturally grounded visual communication guidelines. Infographics offer a promising solution for bridging cultural heritage with the learning needs of contemporary digital audiences.